Hard alloy and processing method, die and tool thereof

By controlling the WC particle size, binder phasor and Cr added amount, the problem of deep corrosion in water-type WEDM is solved, the mold has high wear resistance and crack resistance, and the tool life is extended.

CN119816612APending Publication Date: 2025-04-11FUJI DIE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380062394.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In water-type WEDM, long-term processing of molds of complex shapes or large sizes is prone to deep corrosion, which affects processing accuracy and tool life.

Method used

By controlling the WC particle size, the amount of binder phase and the amount of Cr, a cemented carbide is prepared to ensure that it does not undergo deep corrosion during the water-type WEDM process and has excellent wear resistance and crack resistance.

Benefits of technology

This cemented carbide can effectively prevent shallow corrosion and deep corrosion, improve the wear resistance and crack resistance of the mold, and extend the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816612A_ABST
    Figure CN119816612A_ABST
Patent Text Reader

Abstract

Disclosed is a cemented carbide comprising a hard phase consisting essentially of WC having an average particle size of X [mu] m, and a binder phase consisting essentially of Co having a total amount of Y mass%, in which the addition amount of Cr3C2 and Mo2C relative to the total amount Y of the binder phase is Z mass% (Z = Z1 + 5 / 9Z2, Z1gt; 0 and Z2 > = 0, where the addition amount of Cr3C2 is Z1 mass% and the addition amount of Mo2C is Z2 mass%), and where X, Y, and Z satisfy the following formulae (1), (2), (3), (4), and (5): X < = 6 (1) 4 < = Y < = 20 (2) 0lt; z < = 10X + 5Y-39 (3) Z < = 10X-9 (4) Z < = 11 (5).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cemented carbide and a processing method thereof, as well as a die and a tool made of the same. Background Art

[0002] Cemented carbide has high hardness and excellent wear resistance, and its dimensional changes due to temperature and stress are small, so it is used as a mold material that requires high precision. One of the processing methods for cemented carbide is electrical discharge machining (EDM). EDM can process the workpiece into a complex shape regardless of its hardness as long as it is conductive. For this reason, it is used to manufacture cemented carbide molds with complex shapes or large sizes. EDM can be divided into die-sinking electrical discharge machining (die-sinking electrical discharge machining) and wire cutting electrical discharge machining (Wire Electrical Discharge Machining, WEDM). WEDM usually does not process the workpiece all at once, but moves the wire multiple times on the same contour of the workpiece to complete the specified size and surface roughness.

[0003] The machining fluids used in EDM are divided into two types: oil and water. EDM using oil-type machining fluids has the advantages of excellent machining accuracy and non-corrosion of the workpiece, but has the disadvantages of slow machining speed and the need for fire protection due to its flammability. In contrast, compared with EDM using oil-type machining fluids, EDM using water-type machining fluids has the advantages of fast machining speed and non-flammability, making it safe and suitable for unmanned operation, but has the disadvantages of poor machining accuracy and easy corrosion of the workpiece.

[0004] For these reasons, in WEDM where the wire moves multiple times on the same profile, water-type WEDM is usually used for time-consuming roughing (first cut), and oil-type WEDM is used for subsequent intermediate and finishing. In this case, by switching from water-type WEDM to oil-type WEDM, work efficiency is reduced, and processing accuracy is reduced due to the need to re-set the machine.

[0005] In order to suppress corrosion during EDM using a water-type machining fluid, the following measures are taken in terms of materials and machining devices. In terms of materials, corrosion-resistant cemented carbide for EDM is used. By adding Cr or Cr carbide to a typical WC-Co cemented carbide, or by replacing a portion of Co with Ni, the corrosion resistance of the metal binder phase, which is prone to corrosion, is improved. In addition, the addition of Cr improves the fracture toughness K by solid solution strengthening of the binder phase. IC, which is resistance to crack progression, is expected to have an effect of suppressing thermal cracks during EDM. In terms of machining equipment, corrosion of the workpiece is prevented by adding an anticorrosive agent to a water-type machining liquid or by using an electroless plating power source AE (anti-electrolysis).

[0006] The processing accuracy of water-type WEDM has been improved through technological development by processing equipment manufacturers, and can now meet the processing accuracy requirements of mold applications requiring high dimensional accuracy (such as fine blanking).

[0007] JPH 8-337837 A (Patent Document 1) discloses a cemented carbide for a mold, which contains 5 wt% to 25 wt% of Co and / or Ni as a metal binder phase, wherein the weight ratios of V and Cr to (Co+Ni) are 0.6% to 6.5% and 2.6% to 20%, respectively, and the balance is a WC phase having an average particle size greater than 0.7 μm and less than 6 μm and inevitable impurities, and in addition to the WC phase and the metal binder phase, a carbide phase containing V and Cr is precipitated.

[0008] Japanese Patent Application No. 2003-155538 (Patent Document 2) discloses a cemented carbide for a mold, which contains 6 wt % to 20 wt % of Co and Ni in total, 6 wt % to 10 wt % of Cr (calculated as chromium carbide) relative to the total amount of Co and Ni, and 14 wt % to 30 wt % of Ni relative to the total amount of Co and Ni, wherein the average particle size of tungsten carbide in the alloy is 0.8 to 3 μm, and the balance is tungsten carbide and inevitable impurities.

[0009] JP 2006-152409 A (Patent Document 3) discloses a cemented carbide for a mold, which contains 6 wt % to 20 wt % of Co and Ni in total, 3 wt % to 15 wt % of Cr, 2.5 wt % to 5.0 wt % of V, 1.0 wt % to 5.0 wt % of Mo relative to the total amount of Co and Ni, and 0 wt % to 50 wt % of Ni relative to the total amount of Co and Ni, and the hard phase in the alloy is composed of fine particles and coarse particles of tungsten carbide WC, wherein 60 % to 90 % of the hard phase is fine particles with an average particle size of 0.3 to 0.6 μm, and 10 % to 40 % of the hard phase is coarse particles with an average particle size of 0.8 to 2.5 μm.

[0010] Prior art literature

[0011] Patent Document 1: JPH 8-337837 A

[0012] Patent Document 2: Japanese Patent Application No. 2003-155538

[0013] Patent Document 3: JP 2006-152409 A Summary of the invention

[0014] Purpose of the Invention

[0015] However, in water-type WEDM, due to complex shapes or large-sized molds, etc., the processing circumference is long and the processing time exceeds tens of hours, and corrosion cannot be avoided even if the above-mentioned discharge machining measures are taken. The slight corrosion (shallow corrosion) formed on the surface of the material can be removed in post-processing such as grinding. However, when water-type WEDM is performed on Cr-added cemented carbide for a long time for discharge machining, corrosion (deep corrosion) deep into the material will occur. This deep corrosion requires time to be removed in the above-mentioned post-processing. In addition, there is a problem that the accuracy of the size of the mold decreases as the amount of removal in the post-processing increases. In addition, if the deep corrosion is retained, the tool may have a short life when used.

[0016] In view of the above, for molds that require long processing time and have complex shapes or large sizes, a cemented carbide that can be used with water-based WEDM from rough machining to finishing is required.

[0017] However, for the samples of the embodiment in Patent Document 1, the resistance to corrosion that occurs when immersed in the machining liquid is improved (simple corrosion is reduced), but deep corrosion occurs when water-type WEDM machining is performed for a long time, for example, when discharge machining using water-type machining liquid is performed for a long time from rough machining to finishing.

[0018] Similarly, in the embodiment of patent document 2, the resistance to corrosion that occurs when immersed in the processing liquid is improved (simple corrosion is reduced), but when water-type WEDM processing is performed for a long time, for example, when discharge machining using water-type processing liquid is performed for a long time from rough processing to finishing, deep corrosion occurs.

[0019] The WC-based cemented carbide in Patent Document 3 contains a mixture of fine particles and coarse particles as WC particles to suppress the formation of an altered layer including microcracks formed during EDM. However, due to (1) the small sizes of fine particles and coarse particles and (2) the high ratio of fine particles, deep corrosion occurs when water-based WEDM is performed for a long time.

[0020] Therefore, an object of the present invention is to provide a cemented carbide which prevents slight corrosion (shallow corrosion) from forming on the surface of the material and does not cause deep corrosion penetrating into the interior of the workpiece when electric discharge machining using a water-type machining fluid is performed for a long time from rough machining to finishing.

[0021] Another object of the present invention is to provide a mold and a tool made of such cemented carbide and having excellent wear resistance and chipping resistance.

[0022] Another object of the present invention is to provide a processing method for such cemented carbide.

[0023] Solution

[0024] As a result of intensive research in view of the above problems, the present inventors have found that by controlling the WC grain size, the amount of the binder phase and the amount of Cr added, cemented carbide can prevent shallow corrosion and suppress deep corrosion that occurs when wire-cut electrical discharge machining using a water-based machining liquid is performed for a long time, and is therefore suitable for producing a mold having excellent wear resistance and chipping resistance by water-based WEDM. The present invention was completed based on such a finding.

[0025] The most important point of the present invention is that, unlike the conventional characteristic improvement of electric discharge machining, deep corrosion occurring in cemented carbide when water-based WEDM is performed for a long time is suppressed by controlling the WC grain size, the amount of the binder phase and the amount of Cr added. Conventionally, the corrosion resistance of cemented carbide is measured by the corrosion weight loss and surface roughness change after long-term immersion in a corrosive solution (such as a processing liquid) and the corrosion resistance value R measured by an electrochemical method. Corr However, in such an evaluation method, when the WC particle size is small, the amount of the binder phase is small, and the amount of Cr added is large, the corrosion resistance of the cemented carbide is improved. In the present invention, it has been found that in order to suppress the deep corrosion occurring in long-term water-type WEDM, a larger WC particle size, a larger amount of the binder phase and a smaller amount of Cr added are better. Therefore, it is important to control the WC particle size, the amount of the binder phase and the amount of Cr added to suppress deep corrosion and prevent shallow corrosion. It has also been found that the addition of Mo can even further suppress deep corrosion in an environment containing chlorine.

[0026] Therefore, a cemented carbide according to an embodiment of the present invention includes: a hard phase mainly composed of WC having an average grain size of X μm, and a binder phase mainly composed of Co in a total amount of Y mass%, wherein the addition amount of Cr3C2 and Mo2C is Z mass% (Z=Z1+5 / 9Z2, Z1>0 and Z2≥0, wherein the addition amount of Cr3C2 is Z1 mass%, and the addition amount of Mo2C is Z2 mass%) relative to the total amount Y of the binder phase, and wherein X, Y and Z satisfy the following formulas (1), (2), (3), (4) and (5):

[0027] X≤6… (1)

[0028] 4≤Y≤20… (2)

[0029] 0 <Z≤10X+5Y-39… (3)

[0030] Z≤10X-9… (4)

[0031] Z≤11… (5).

[0032] In the cemented carbide of the present invention, the average particle size X preferably satisfies the following formula (6):

[0033] 3 <X… (6),

[0034] And more preferably, the following formula (7) is satisfied:

[0035] X<6… (7).

[0036] In the cemented carbide of the present invention, the total amount Y of the binder phase preferably satisfies the following formula (8):

[0037] 5 <Y<20… (8)。

[0038] And the average particle size X of the hard phase and the total amount Y of the binder phase preferably satisfy the following formula (9):

[0039] Y≤19-2X… (9).

[0040] In the cemented carbide of the present invention, the addition amount Z of Cr3C2 and Mo2C relative to the total amount Y of the binder phase preferably satisfies the following formula (10):

[0041] 0.3≤Z≤11… (10).

[0042] The cemented carbide of the present invention preferably contains Ni in an amount of 30% by mass or less relative to the binder phase, and when the addition amount of Co relative to the binder phase is Y1% by mass and the addition amount of Ni is Y2% by mass, they preferably satisfy the following formula (11):

[0043] 0.2≤Y2 / (Y1+Y2)≤0.3… (11).

[0044] In the cemented carbide of the present invention, the addition amount Z1 of Cr3C2 and the addition amount Z2 of Mo2C preferably satisfy the following formula (12):

[0045] 0<5 / 9Z2 / (Z1+5 / 9Z2)<0.8… (12).

[0046] In the cemented carbide of the present invention, it is preferred that the bending strength is 2000 MPa or more, and the decrease rate of the bending strength after the wire cut electrical discharge machining test under the wire cut electrical discharge machining test conditions shown below is less than 35%.

[0047] Wire EDM Test Conditions

[0048] Processing liquid: deionized water

[0049] Wire material: Brass

[0050] Wire diameter: 0.3 mm

[0051] Cutting times: 11 times

[0052] Processing time: 22 hours

[0053] Processing circumference: 400 mm.

[0054] A mold according to one embodiment of the present invention is made of the above-mentioned cemented carbide.

[0055] The mold is preferably produced by subjecting at least a portion of the above-mentioned cemented carbide to wire-cut electrical discharge machining using a water-based machining fluid.

[0056] A tool according to one embodiment of the present invention is made of the above-mentioned cemented carbide.

[0057] The tool is preferably produced by subjecting at least a portion of the above-mentioned cemented carbide to wire-cut electrical discharge machining using a water-based machining fluid.

[0058] A machining method for cemented carbide according to one embodiment of the present invention includes subjecting the above-mentioned cemented carbide to wire-cut electric discharge machining using a water-type machining liquid.

[0059] Effects of the Invention

[0060] According to the present invention, by controlling the WC particle size, the amount of the binder phase and the amount of the element added, a cemented carbide can be obtained, which can prevent shallow corrosion while suppressing deep corrosion that occurs during long-term electrical discharge machining using a water-based machining liquid, and is suitable for molds with complex shapes or large sizes that require electrical discharge machining. The mold manufactured by the cemented carbide of the present invention through water-based WEDM can prevent deep corrosion as well as shallow corrosion, and has excellent wear resistance and chipping resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 : is a graph showing the relationship between the average grain size X of the hard phase, the total amount Y of the binder phase, and the addition amount Z of Cr3C2 and Mo2C.

[0062] Figure 2 : are optical microscope photographs of cross sections showing corrosion that occurs when the Cr-free comparative product 2 and the Cr-containing comparative product 6 having cracks are immersed in a water-type processing liquid (deionized water).

[0063] Figure 3It is a diagram showing the approximate positions of the inventive product and the comparative product in the relationship between the average grain size X of the hard phase, the total amount Y of the binder phase, and the addition amounts Z of Cr3C2 and Mo2C relative to the binder phase.

[0064] Figure 4 : are optical microscope photographs showing the corrosion states of samples of the inventive products 8 and 10 and the comparative products 2, 5, 6 and 9 after a long-term water-type WEDM test. DETAILED DESCRIPTION

[0065] [1] Cemented Carbide

[0066] A cemented carbide according to an embodiment of the present invention includes: a hard phase mainly composed of WC having an average grain size of X μm, and a binder phase mainly composed of Co in a total amount of Y mass %, wherein the addition amount of Cr3C2 and Mo2C is Z mass % (Z=Z1+5 / 9Z2, Z1>0 and Z2≥0, wherein the addition amount of Cr3C2 is Z1 mass % and the addition amount of Mo2C is Z2 mass %) relative to the total amount Y of the binder phase, and wherein X, Y and Z satisfy the following formulas (1), (2), (3), (4) and (5):

[0067] X≤6… (1)

[0068] 4≤Y≤20… (2)

[0069] 0 <Z≤10X+5Y-39… (3)

[0070] Z≤10X-9… (4)

[0071] Z≤11… (5).

[0072] Figure 1 The relationship between the average grain size X of the hard phase, the total amount Y of the binder phase, and the addition amount Z of Cr3C2 and Mo2C is shown.

[0073] The average particle size X of the hard phase is 6 μm or less. Based on the structure of any cross section of the cemented carbide, the average particle size X of the hard phase is calculated by the Fullman formula. When the average particle size X of the hard phase exceeds 6 μm, the number of thick parts of the binder phase increases, the hardness decreases, the wear resistance and the chipping resistance deteriorate, the bending strength is significantly reduced, and in addition to the shallow corrosion (surface corrosion) formed on the surface of the material, the deep corrosion (crevice corrosion) deep into the material also becomes significant. Shallow corrosion is corrosion that occurs when the cemented carbide is immersed in a water-based processing liquid. On the other hand, deep corrosion is corrosion that occurs when water-based WEDM processing is performed for a long time, and it is believed that the cracks generated in the water-based WEDM cause gaps during long-term processing when the wire is moved many times, thereby causing crevice corrosion. From the viewpoint of reducing shallow corrosion and further improving wear resistance and chipping resistance, the average particle size X of the hard phase is preferably less than 6 μm, more preferably less than 5.5 μm, further preferably less than 4.5 μm, further preferably less than 3.8 μm, and further preferably less than 3.5 μm. Furthermore, from the viewpoint of reducing shallow corrosion and inhibiting deep corrosion, the average grain size X of the hard phase is preferably larger than 3 μm.

[0074] In addition to the WC phase (WC particles) as the main component, the hard phase may contain at least one phase in which carbides, nitrides and carbonitrides of metals of Groups 4 to 6 of the periodic table (such as (Ta, Nb) C, (W, Ti) C, (W, Cr, Ti) C, (W, Ti) CN, (W, Ti, Nb) C, etc.) are dissolved. The average particle size of the solid solution phase is preferably 0.5 to 2 μm. The amount of the solid solution phase is preferably 10% by mass or less of the hard phase.

[0075] The total amount Y of the binder phase is within the range of more than 4% by mass and less than 20% by mass. Here, the total amount Y of the binder phase represents the sum of the components added as binder phase components, and the components dissolved in the binder phase after addition as other components are not included in the total amount Y of the binder phase. When the total amount Y of the binder phase is less than 4% by mass, the sintering property deteriorates, and the hardness of the cemented carbide becomes too high, and the bending strength is significantly reduced, so deep corrosion may occur. When the total amount Y of the binder phase is greater than 20% by mass, the wear resistance when used as a tool is poor. The total amount Y of the binder phase is preferably greater than 5% by mass, and preferably less than 20% by mass.

[0076] In addition to the main component Co, the binder phase may contain 30% by mass of Ni relative to the total amount of the binder phase, and 20% by mass of Ni may further bring advantages without deteriorating the properties. In the binder phase, when the addition amount of Co is Y1% by mass and the addition amount of Ni is Y2% by mass, the following formula (6) is preferably satisfied:

[0077] 0.2≤Y2 / (Y1+Y2)≤0.3… (6).

[0078] It can also contain the component that can be used as binder phase, such as Fe, Al and Cu.These components are included in the component added as above-mentioned binder phase component.In addition, the metallic element constituting hard phase can be dissolved in the binder phase of cemented carbide.When comprising the component except Co as the binder phase component as above, the amount of Co relative to the total amount of binder phase is preferably more than 70 mass %, and more preferably more than 80 mass %.

[0079] In the cemented carbide of the present invention, Cr3C2 is added as an essential element, and its addition amount Z1 is greater than 0 mass % and less than 11 mass %. The addition of Cr3C2 inhibits the grain growth of WC during sintering and improves corrosion resistance. When the addition amount Z1 of Cr3C2 exceeds 11 mass %, the third phase composed of complex carbides is easily precipitated, and the rate of decrease of bending strength after water-type WEDM increases, which is easy to cause deep corrosion. The addition amount Z1 of Cr3C2 is preferably 0.3 mass % or more, more preferably 0.7 mass % or more, further preferably 1 mass % or more, and further preferably 2 mass % or more.

[0080] In addition to Cr3C2, Mo2C can also be added. Mo2C is not as good as Cr3C2 in improving corrosion resistance, but it shows an excellent corrosion resistance improvement effect, especially when exposed to chlorine or chlorine-based compounds. When the addition amount of Cr3C2 is Z1 mass% and the addition amount of Mo2C is Z2 mass%, the addition amount of Cr3C2 and Mo2C Z=Z1+5 / 9Z2 is greater than 0 mass% and is less than 11 mass%. When the addition amount Z of Cr3C2 and Mo2C is greater than 11 mass%, the third phase composed of complex carbides is easily precipitated, and the rate of decrease of bending strength after water-type WEDM increases, which is easy to cause deep corrosion. The addition amount Z of Cr3C2 and Mo2C is preferably 0.3 mass% or more, more preferably 0.7 mass% or more, further preferably 1 mass% or more, and further preferably 2 mass% or more.

[0081] The addition amount Z1 of Cr3C2 and the addition amount Z2 of Mo2C satisfy the following formula (7):

[0082] 0<5 / 9Z2 / (Z1+5 / 9Z2)<0.8… (7).

[0083] When 5 / 9Z2 / (Z1+5 / 9Z2) is less than 0.8, the corrosion resistance improvement effect of Cr3C2 is fully exerted, and a cemented carbide with a long life can be obtained even in an environment exposed to chlorine or chlorine compounds. The addition amount Z1 of Cr3C2 and the addition amount Z2 of Mo2C more preferably satisfy 5 / 9Z2 / (Z1+5 / 9Z2)<0.7.

[0084] VC may be added in an amount of 5% by mass or less relative to the total amount of the binder phase. Cr3C2, VC and Mo2C may be added partially or entirely by using metal powders containing the same amount of metal elements Cr, V and Mo or other compounds containing the same amount of metal elements. In these cases, the addition amount is calculated as carbide.

[0085] When the amount of binder phase Y is 6≤Y≤20, the average particle size X of the hard phase and the addition amount Z of Cr3C2 and Mo2C satisfy the following formula (4):

[0086] Z≤10X-9… (4).

[0087] When the average particle size X of the hard phase increases with the increase of the addition amount Z of Cr3C2 and Mo2C, the rate of decrease of the bending strength after water-based WEDM can be reduced and the occurrence of deep corrosion can be suppressed. It is generally believed that the more Cr (or if Mo is contained, Cr and Mo) contained in the cemented carbide, the better the corrosion resistance. However, the research of the inventors shows that the addition of Cr is not effective enough for the above-mentioned deep corrosion. After mechanically introducing cracks into the following Cr-free alloy (Comparative Product 2) and Cr-containing alloy (Comparative Product 6), the alloy was immersed in a water-based processing liquid (deionized water) for 24 hours. The cross-section of the formed corrosion area is shown in Figure 2 In the optical microscope photo. Figure 2 As shown in FIG. 1 , the comparative product 6 containing Cr completely suppressed surface corrosion compared to the comparative product 2, but had crevice corrosion occurring inside. Based on this finding, the present inventors have found that Figure 1 As shown in the surface 1, when the addition amount Z of Cr3C2 and Mo2C relative to the total amount Y of the binder phase is within the range of greater than 0 mass % and less than 11 mass %, by setting the average particle size X of the hard phase to greater than 0.9 μm when the amount Z of Cr3C2 and Mo2C is greater than 0 mass %, and setting the average particle size X of the hard phase to a value equal to or greater than the value satisfying the relationship Z=10X-9, shallow corrosion can be prevented and deep corrosion can be suppressed. When the addition amount Z of Cr3C2 and Mo2C exceeds 10X-9, the decrease rate of the bending strength after water-type WEDM increases significantly, and deep corrosion may occur. The average particle size X of the hard phase and the addition amount Z of Cr3C2 and Mo2C preferably satisfy the following formula (8):

[0088] Z≤10X-13… (8),

[0089] More preferably, the following formula (9) is satisfied:

[0090] Z≤10X-16… (9).

[0091] When the amount of binder phase Y is 4≤Y≤6, the average particle size X of the hard phase, the total amount Y of the binder phase, and the addition amount Z of Cr3C2 and Mo2C satisfy the following formula (3):

[0092] 0 <Z≤10X+5Y-39… (3)。

[0093] As the addition amount Z of Cr3C2 and Mo2C increases, the average particle size X of the hard phase increases. In addition, in order to suppress the occurrence of deep corrosion, especially when the total amount Y of the binder phase is small, the average particle size X needs to be further increased as the total amount Y of the binder phase decreases. Based on this discovery, the inventors have found that Figure 1 As shown in the surface 2, when the total amount Y of the binder phase is in the range of 4 mass % or more and 6 mass % or less, by setting the average particle size X of the hard phase to be greater than 0.9 μm when the total amount Y of the binder phase is 6 mass % and the addition amount Z of Cr3C2 and Mo2C is greater than 0 mass %, and setting the average particle size X of the hard phase to be equal to or greater than the value satisfying the relationship Z=10X+5Y-39, shallow corrosion can be prevented and deep corrosion can be suppressed. When the addition amount Z of Cr3C2 and Mo2C exceeds 10X+5Y-39, the rate of decrease in bending strength after water-type WEDM increases, and deep corrosion may occur. The average particle size X is more preferably 1.8 μm or more, and further preferably 1.9 μm or more.

[0094] When the average particle size X of the hard phase is 4.5 μm or less, the average particle size X and the total amount Y of the binder phase preferably satisfy the following formula (10):

[0095] Y≤19-2X… (10).

[0096] When the total amount Y of the binder phase is 19-2X or less, shallow corrosion is prevented, the occurrence of deep corrosion is suppressed, and wear resistance is improved while maintaining high chipping resistance. When the average particle size X is 3.5 μm or less, the average particle size X of the hard phase and the total amount Y of the binder phase more preferably satisfy the following formula (11):

[0097] Y≤17-2X… (11).

[0098] The bending strength of the cemented carbide of the present invention is preferably 2000 MPa or more. The bending strength is determined by a three-point bending test based on JIS R1601. When the bending strength is less than 2000 MPa, fracture and cracking may occur. The bending strength of the cemented carbide is more preferably 2700 MPa or more.

[0099] In the cemented carbide of the present invention, the decrease rate of the bending strength after the wire cut electrical discharge machining (water type WEDM) test under the wire cut electrical discharge machining test conditions shown below is preferably less than 35%.

[0100] Wire EDM Test Conditions

[0101] Processing liquid: deionized water

[0102] Wire material: Brass

[0103] Wire diameter: 0.3 mm

[0104] Cutting times: 11 times

[0105] Processing time: 22 hours

[0106] Processing circumference: 400 mm

[0107] When the decrease rate of bending strength is less than 35%, cracks caused by water-type WEDM are shorter and the occurrence of deep corrosion can be suppressed. The decrease rate of bending strength is more preferably 33% or less, and further preferably 30% or less.

[0108] The Vickers hardness of the cemented carbide of the present invention is preferably 1150 to 1600 HV. When the Vickers hardness is less than 1150 HV, wear resistance is insufficient, and when the Vickers hardness is greater than 1600 HV, chipping may occur. The Vickers hardness of the cemented carbide is more preferably 1250 to 1500 HV.

[0109] The fracture toughness K represents the toughness of the cemented carbide of the present invention. IC Preferably 16 MPa·m 1 / 2 Fracture toughness K IC Calculated from the crack length generated at the corner of the Vickers indentation based on JIS R 1607. IC Less than 16MPa·m 1 / 2 When the fracture is likely to occur. Fracture toughness K IC More preferably, 18 MPa·m 1 / 2 above.

[0110] An example of a manufacturing method for cemented carbide is described below. The raw material powder is wet mixed in a ball mill or the like, and then dried to prepare a molding powder, which will be the material of the cemented carbide. The molding powder is molded by methods such as mold molding, cold isostatic pressing (CIP), etc. The obtained green body is sintered in a vacuum or inert atmosphere at a temperature equal to or higher than the liquid phase appearance temperature. The liquid phase appearance temperature of the green body is the temperature at which the liquid phase begins to appear during the temperature increase process of sintering, and is measured using a differential thermal analyzer. The upper limit of the sintering temperature is preferably the liquid phase appearance temperature + 100 ° C. The obtained sintered body can be further subjected to HIP treatment.

[0111] As described above, the cemented carbide of the present invention can be applied to water-type WEDM, but even when it is used for electrical discharge machining other than water-type WEDM (such as WEDM machining or die-cutting electrical discharge machining using oil as a machining liquid), it can produce workpieces with high chipping resistance and wear resistance, while minimizing the rate of decrease in bending strength after machining and suppressing the occurrence of corrosion and cracks. Such workpieces are not limited to molds, but can be any tools that can be given a precise shape by electrical discharge machining, including molds, cutting tools, wear-resistant tools, shear knives, various machine parts, etc. In addition, even for parts that are not subjected to electrical discharge machining, they can be used for parts where crevice corrosion is a problem, taking advantage of their characteristics that they are not susceptible to deep corrosion.

[0112] [2] Processing methods for cemented carbide

[0113] The method for processing the above-mentioned cemented carbide of the present invention is characterized in that the cemented carbide is subjected to wire cutting electrical discharge machining (water type WEDM) using a water type machining liquid. Deionized water is preferably used as the machining liquid. There is no particular restriction on the equipment used for wire cutting electrical discharge machining, and any general equipment for wire cutting electrical discharge machining using a water type machining liquid is applicable. The processing method for cemented carbide of the present invention is particularly suitable for manufacturing molds with complex shapes or large sizes that require long-term processing, and can be used for electrical discharge machining using a long-term water type machining liquid from rough processing to fine processing.

[0114] [3] Mould

[0115] The mold of the present invention is made of the above-mentioned cemented carbide, and in particular, it is preferred that at least a portion of the above-mentioned cemented carbide has been subjected to wire cutting electric discharge machining using a water-type machining liquid. The mold of the present invention is preferably a molding mold having a complex shape or a large size. By subjecting the above-mentioned cemented carbide to wire cutting electric discharge machining using a water-type machining liquid, even when the mold has such a complex shape or a large size, a mold having excellent wear resistance and chipping resistance can be obtained while preventing shallow corrosion and suppressing the occurrence of deep corrosion.

[0116] Example

[0117] The present invention is specifically described below by way of examples, but the present invention is not limited thereto.

[0118] Example 1

[0119] As raw material powders, WC powder, Co powder (1.4 μm), Ni powder (2.4 μm), Cr3C2 powder (2.4 μm) and Mo2C powder (3.6 μm) with different particle sizes were used. The average particle size of the WC powder is shown in Table 1. The average particle size of the powder was measured by the FSSS method. These powders were mixed according to the composition shown in Table 1, wet mixed, and dried to obtain a mixed powder. The mixed powder was press-formed, and the resulting green body was sintered at 1400°C in a vacuum, and then HIP treated at 1400°C to produce a cemented carbide.

[0120] Table 1

[0121]

[0122] The average particle size of the hard phase (WC particles in the alloy) of the cemented carbides of the invention products 1 to 15 and the comparative products 1 to 11 was calculated using the Fullman formula. The results are shown in Table 2. The approximate positions of the invention products and the comparative products in the relationship between the average particle size X of the hard phase, the total amount Y of the binder phase, and the addition amount Z of Cr3C2 and Mo2C relative to the binder phase are shown in Table 2. Figure 3 middle.

[0123] Table 2

[0124]

[0125] The Vickers hardness, bending strength and fracture toughness K of the cemented carbides of the invention products 1 to 15 and the comparative products 1 to 11 were measured. IC Vickers hardness was measured using a Vickers hardness tester HV30. Flexural strength was measured by a three-point bending test based on JIS R 1601, where the #140 flat ground surface before water-type WEDM was used as the tensile forces surface. Fracture toughness K IC The calculation was performed based on JIS R 1607 from the crack length generated at the corner of the Vickers indentation.

[0126] The cemented carbide of Comparative Product 1 has a very small amount of binder phase of 2 mass %, so it is not fully densified during sintering and HIP treatment, resulting in the appearance of pores and a significantly reduced bending strength of 1320 MPa, making it impossible to use as a mold. The cemented carbide of Comparative Product 8 has a very large average grain size of alloy WC particles and a very low bending strength of 1720 MPa, making it impossible to use as a mold. The cemented carbide of Comparative Product 11 has a very large Cr3C2 addition amount of about 14 mass % relative to the amount of the binder phase, so Cr carbides precipitate and it cannot be used as a mold.

[0127] Example 2

[0128] The cemented carbides of the invention products 1 to 15 and the comparative products 2 to 7, 9 and 10 were subjected to a water-type WEDM test. The water-type WEDM test was performed by wire-cutting discharge machining (wire material: brass, wire diameter: 0.3 mm, number of cuts: 11 times, machining time: 22 hours) using deionized water as the machining liquid, and the bending strength after the water-type WEDM and the type and amount of corrosion were studied. The bending strength after the water-type WEDM was measured by a three-point bending test based on JIS R 1601, with the water-type WEDM surface as the tensile surface. The samples after the water-type WEDM test were observed under an optical microscope, and when there was only shallow corrosion, it was marked as excellent, when there was a small amount of deep corrosion, it was marked as good, and when there was a large amount of deep corrosion, it was marked as poor. The amount of corrosion was compared with the amount of corrosion in the comparative product 5, which is one of the materials close to the existing mold material, and regardless of the type, if the amount is less, it is marked as excellent; if the amount is the same, it is marked as good; and if the amount is larger, it is marked as poor. The results are shown in Table 3. In addition, optical microscope photographs (magnification: 100x) showing the corrosion state of the samples of the invention products 8 and 10 and the comparative products 2, 5, 6 and 9 after the long-term water type WEDM test are shown in Figure 4 middle.

[0129] Table 3

[0130]

[0131] like Figure 4 As shown, in the invention products 8 and 10, no deep corrosion occurred, and very little shallow corrosion was observed. In the comparative product 2, shallow corrosion occurred, and a small amount of deep corrosion was also observed. A large amount of deep corrosion occurred in the comparative products 5, 6, and 9, and the deep corrosion of the comparative products 6 and 9 was particularly significant.

[0132] Example 3

[0133] Actual tests were conducted to evaluate the practical use of the cemented carbides of the invention products 1 to 15 and the comparative products 2 to 7, 9 and 10 as mold materials. The cemented carbides of the invention products 1, 2, 5, 8, 10, 14 and 15 and the comparative products 5 to 7 and 9 were used to prepare molds by 29 hours of water-type WEDM, and a stamping test of a steel plate was performed. The cemented carbides of the invention products 3 and 11 and the comparative products 2 and 6 were used to prepare molds by 29 hours of water-type WEDM, and an aluminum deformation tensile test was performed. The cemented carbides of the invention products 4, 12 and 13 and the comparative products 3 and 10 were used to prepare molds by 29 hours of water-type WEDM, and a hot forging test was performed. The cemented carbides of the invention products 5 to 7 and the comparative product 5 were used to prepare molds by 29 hours of water-type WEDM, and a deep tensile test was performed using a processing oil containing a chlorine-based extreme pressure additive. The cemented carbides of the invention product 9 and the comparative products 4 and 10 were used to prepare molds by 29 hours of water-type WEDM, and a cold forging test was performed. When it was excellent as a tool for long-term water-type WEDM, it was marked as excellent, when it was practical, it was marked as good, and when it was not practical, it was marked as poor. The results are shown in Table 4.

[0134] Table 4

[0135]

[0136] As shown in Tables 1 to 4, the amount of corrosion of the cemented carbides of Inventive Products 1, 2, 5, 14, and 15 after long-term water-type WEDM was equal to that of Comparative Product 5, but no deep corrosion occurred, and the punching test confirmed that they can be used as molds. Even after long-term water-type WEDM, no deep corrosion occurred in the cemented carbides of Inventive Products 8 and 10, and the amount of corrosion including shallow corrosion was small. In the punching test, they showed excellent wear resistance. Deep corrosion occurred in the cemented carbides of Comparative Products 5 to 7 and 9, so they are not suitable for actual use in punching tests.

[0137] Even after long-term water-type WEDM, no deep corrosion occurred and a small amount of shallow corrosion occurred in the cemented carbides of the invention products 3 and 11, and they showed excellent wear resistance in the tensile test. A small amount of deep corrosion and a large amount of shallow corrosion occurred in the cemented carbide of the comparative product 2, which led to die cracking during the tensile test. Deep corrosion occurred in the cemented carbide of the comparative product 6, and thus die cracking occurred during the tensile test.

[0138] The amount of corrosion of the cemented carbide of invention product 4 after long-term water-type WEDM is equal to that of comparison product 5, but no deep corrosion occurs. In the hot forging test, rough surface and wear caused by corrosion were observed, but it was confirmed that it was actually usable. The cemented carbide of invention product 12 has less corrosion than invention product 4, and because it contains a larger amount of Cr3C2, it also has improved oxidation resistance and surface roughness, and shows excellent wear resistance. Compared with invention product 12, invention product 13 contains Ni in the binder phase, and further improves oxidation resistance and surface roughness. The cemented carbides of comparison products 3 and 10 show a small amount of deep corrosion, but also show a large amount of shallow corrosion, which leads to damage.

[0139] After long-term water-type WEDM during mold production, the amount of corrosion of the cemented carbide of Invention Product 5 was equal to that of Comparative Product 5, and no deep corrosion occurred. However, due to the water-type WEDM finishing in the final production process, fine cracks remained in some parts of the finished product, and corrosion occurred due to the influence of the chlorine component contained in the processing oil during the deep drawing test, resulting in wear from there, resulting in a slightly shorter life than other invention products. The amount of corrosion of the cemented carbide of Invention Product 6 after long-term water-type WEDM was equal to that of Invention Product 5 and Comparative Product 5, but no deep corrosion occurred. In addition, even when used in the presence of chlorine, corrosion was suppressed, confirming that Invention Product 6 can be used as a deep drawing die even when compared with Invention Product 5. Even during long-term water-type WEDM, no deep corrosion occurred in the cemented carbide of Invention Product 7, and the amount of corrosion, including shallow corrosion, was small. Even in the presence of chlorine, cemented carbide shows excellent life in actual use as a deep drawing die. Deep corrosion occurred in the cemented carbide of Comparative Product 5, and when used in the presence of chlorine, the corrosion further progressed and the material wore away, resulting in a short life.

[0140] The amount of corrosion of the cemented carbide of the invention product 9 after long-term water-type WEDM is equal to that of the comparative product 5, but no deep corrosion occurs, and it shows excellent wear resistance in the cold forging test. The cemented carbides of the comparative products 4 and 10 show a small amount of deep corrosion, but also a large amount of shallow corrosion, which causes wear and tear of the WC, resulting in a short life.

[0141] As described above, it has been found that according to the present invention, a cemented carbide can be obtained which has excellent bending strength before and after water type WEDM and has practical corrosion resistance that does not cause deep corrosion even when water type WEDM is performed for a long time.

Claims

1. A cemented carbide, comprising: A hard phase mainly composed of WC having an average particle size of X μm, and a binder phase mainly composed of Co in a total amount of Y mass%, wherein the addition amount of Cr3C2 and Mo2C is Z mass% (Z=Z1+5 / 9Z2, Z1>0 and Z2≥0, wherein the addition amount of Cr3C2 is Z1 mass% and the addition amount of Mo2C is Z2 mass%) relative to the total amount Y of the binder phase, and wherein X, Y and Z satisfy the following formulas (1), (2), (3), (4) and (5): X≤6… (1) 4≤Y≤20… (2) 0 <Z≤10X+5Y-39… (3) Z≤10X-9… (4) Z≤11… (5)。 2. The cemented carbide according to claim 1, wherein the average particle size X satisfies the following formula (6): 3<X… (6)。 3. The cemented carbide according to claim 1 or 2, wherein the average particle size X of the hard phase satisfies the following formula (7): X<6… (7)。 4. The cemented carbide according to any one of claims 1 to 3, wherein the total amount Y of the binder phase satisfies the following formula (8): 5<Y<20… (8)。 5. The cemented carbide according to any one of claims 1 to 4, wherein the average particle size X of the hard phase and the total amount Y of the binder phase satisfy the following formula (9): Y≤19-2X… (9).

6. The cemented carbide according to any one of claims 1 to 5, wherein the addition amount Z of Cr3C2 and Mo2C relative to the total amount Y of the binder phase satisfies the following formula (10): 0.3≤Z≤11… (10)。 7 . The cemented carbide according to claim 1 , wherein the cemented carbide contains Ni in an amount of 30 mass % or less relative to the binder phase.

8. The cemented carbide according to any one of claims 1 to 7, wherein When the addition amount of Co in the binder phase is Y1 mass % and the addition amount of Ni is Y2 mass %, they satisfy the following formula (11): 0.2≤Y2 / (Y1+Y2)≤0.3… (11).

9. The cemented carbide according to any one of claims 1 to 8, wherein The addition amount Z1 of Cr3C2 and the addition amount Z2 of Mo2C satisfy the following formula (12): 0<5 / 9Z2 / (Z1+5 / 9Z2)<0.8… (12).

10. The cemented carbide according to any one of claims 1 to 9, wherein The bending strength is 2000 MPa or more, and the decrease rate of the bending strength after the wire cut electric discharge machining test under the wire cut electric discharge machining test conditions shown below is less than 35%, Wire EDM Test Conditions Processing liquid: deionized water Wire material: Brass Wire diameter: 0.3 mm Cutting times: 11 times Processing time: 22 hours Processing circumference: 400 mm.

11. A mold made of the cemented carbide according to any one of claims 1 to 10. 12 . A mold produced by subjecting at least a portion of the cemented carbide according to claim 1 to wire-cut electrical discharge machining using a water-based machining fluid.

13. A tool made of the cemented carbide according to any one of claims 1 to 10.

14. A tool produced by subjecting at least a portion of the cemented carbide according to any one of claims 1 to 10 to wire-cut electrical discharge machining using a water-based machining fluid.

15. A processing method for cemented carbide, the processing method comprising subjecting the cemented carbide according to any one of claims 1 to 10 to wire-cut electric discharge machining using a water-type processing fluid.

Citation Information

Patent Citations

  • High hardness and high toughness cemented carbide and impact type impact rotor

    JP1997125185A

  • Hard metal alloy, tool for plastic working, and machining tool

    JP2003113437A

  • Cemented carbide and cutting tool

    JP2020132972A

  • Cemented carbide cutter

    JP2022136020A

  • Ni-added WC-Co-based cemented carbide or tools made therefrom

    JP5606612B1